A framework for risk assessment in collaborative networks to promote sustainable systems in innovation ecosystems - Santos, Ricardo (2020)
Nowadays-and due to an increasingly competitive world-organizations need to collaborate in an open innovation context to be efficient and effective by achieving high levels of innovation with their products and services. However, the existing resources-as well as the innovation achieved from the diversity of partners involved-brings challenges to the management; in particularly with risk management. To fulfill such needs, risk management frameworks have been created to support managers, on preventing threats with systems development, although without properly account the influence of each system component, on the entire system, as well as the subjectivity within human perception. To account for these issues, a framework supported by fuzzy logic is presented in this work, to evaluate the risk level on system development in open innovation environment. The approach robustness is assessed by using a case study, where the challenges and benefits found are discussed.